(untitled) (University Journal of Zoology, Rajshahi University, 2013)
The study was carried out in Chittagong Veterinary and Animal Sciences University (CVASU), Chittagong to find out the causes of sudden death of cattle in the Military Dairy Farm, Chittagong. To explore the cause of death, clinical history, clinical signs were recorded. Finally, postmortem was done and samples were collected for laboratory diagnosis. The ruminal pH was 9.0 and the clinical history along with signs suggests possible non-protein nitrogenous compound poisoning. The laboratory diagnosis coincides with nitrate poisoning which focuses possible relationship between non-protein nitrogenous compound and nitrate poisoning. The study recommends maintaining proper cautions to use urea in concentrate feed. DOI: http://dx.doi.org/10.3329/ujzru.v31i0.15403 Univ. j. zool. Rajshahi Univ. Vol. 31, 2012 pp. 65-68